Seasonal shifts in the thermal biology of the lizard Liolaemus tandiliensis (Squamata, Liolaemidae). (April 2018) - Stellatelli, Oscar Aníbal; Villalba, Agustina; Block, Carolina; Vega, Laura Estela; Dajil, Juan Esteban; Cruz, Félix Benjamín
Abstract: Small lizards can accommodate to constraints imposed by temporal changes in ambient temperature through a combination of adaptive evolution and behavioral and physiological plasticity. Thermal physiology plasticity may compensate for climate variation and favor performance while minimizing behavioral costs in sub-optimal conditions. The Tandilia's lizard, Liolaemus tandiliensis, occurs in an isolated mountain range of the Argentinean temperate Pampas. In this study, we compared the thermal biology of L . tandiliensis between late spring (December) and mid-summer (February). The habitats' thermal quality was lower in late spring than in mid-summer. The lizard's field-body temperature ( T b) was 2–3 °C higher than the operative temperature ( T e). Overall, the mean preferred temperature ( T sel) was 37.4 °C [preferred range ( T set): 36.2–38.7 °C], and was similar to other Liolaemus species. The T set and T sel of females in late spring were 1.8 °C lower than in mid-summer. In the case of males, the T sel did not vary among seasons, while the T set had a difference of 2.5 °C between seasons. Adults were moderate thermoregulators, but females were more efficient only in late spring ( E males = 0.69; E females = 0.58), compared to mid-summer ( E males = 0.68; E females = 0.50). Juveniles did not show temporal differences in temperature preferences and had a relatively higher efficiency in late spring ( E = 0.38) compared to mid-summer ( E = 0.28). An increased proportion of juveniles and adults shifted their T b near to the T set in late spring respect to mid-summer. The adults also matched their preferred temperatures to their current body temperature. These results suggest that seasonal shifts in the thermoregulatory parameters of L . tandiliensis may improve their thermoregulatory efficiency. Although temporal variation in ambient temperatures might influence the thermal biology of the studied lizards, other factors such as changes in the reproductive status may have also interfered. Highlights: We studied the thermal biology of Liolaemus tandiliensis . Thermal quality of the habitat and adults' preferred temperature decreased in spring. Thermoregulatory efficiency of L . tandiliensis was higher in spring than in summer. This plasticity may be associated with thermal seasonality of the habitat. Acclimatization may maximize performance during reproduction in spring.